علماے دیوبند کی منتخب کُتبِ فتاویٰ:: ایک تجزیاتی مطالعہ - ڈاکٹر حافظ غلام یوسف (FIKR-O NAZAR فکر ونظر, 2014)
This paper presents an overview of ten selected works on Fatwa literature produced by the jurists of Deoband School. Studying these in chronological order, the author identifies various legal debates and deliberations that continue to appear on the intellectual scene with the march of time. These works also depict the challenges faced by the Muslim community during colonial and post colonial era.